„Międzynarodowe życie rzeczy” w świetle „międzynarodowego życia osób” - Hordecki, Bartosz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2014)
The text emphasises that in European culture, the terms ‘thing’ and ‘person’, as well as ‘subject and ‘object’, alongside their synonyms, have been changing their meanings, or rather acquiring new ones. Particular attention is given to the presentation of the following: 1. the transformation of the language used in the late Middle Ages which was most likely to have facilitated the modern transformation in thinking about the state and the individual (Ockham, nominalism); 2. parallelism of the modern concept of the state as subject (Richelieu, the concept of sovereignty) and the modern concept of the individual as subject (Descartes, the concept of autonomy). It is also indicated that since the 17th century the belief in the sovereignty of the state has alternated with the autonomy of the individual. Consequently, various types of objectification (for example, when individuals’ powers are diminished for the sake of the state, or the other way around). Describing the relations of subjectivity-objectivity and subjectification- objectification their flagrantly dichotomous nature is emphasised, which has entrenched itself as a consequence of European logic. It is also stressed, however, that relentlessly contrasting ‘subjects’ with ‘objects’ and ‘things’ with ‘persons’ continues to constitute one of the foundations of Europeanness.